Phrenic nerve stimulation in CRT patients and benefits of electronic lead repositioning: the ERACE trial - Götze, Stephan; Defaye, Pascal; Bauer, Alexander; Merkel, Matthias; Bizeau, Olivier; Treusch, Sven; Contzen, Klaus; Jünger, Claus Heinrich; Winter, Joachim (Journal of interventional cardiac electrophysiology, 2013)
Despite novel left ventricular (LV) lead technologies, phrenic nerve stimulation (PNS) remains an adverse effect observed in many patients with cardiac resynchronization therapy (CRT). Beyond anatomic repositioning, modern CRT devices allow avoidance of PNS also by software-based adaption of the pacing configuration. The Electronic Repositioning With Acuity and Easytrak Leads study evaluated the incidence of PNS in a CRT population and examined how often LV lead relocation can be avoided by “electronic repositioning” (ER).
Gesehen am 12.02.2020